2021
DOI: 10.2196/26471
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Mobile Health-Related Apps: Interrater Reliability Study of Two Guides

Abstract: Background There is a huge number of health-related apps available, and the numbers are growing fast. However, many of them have been developed without any kind of quality control. In an attempt to contribute to the development of high-quality apps and enable existing apps to be assessed, several guides have been developed. Objective The main aim of this study was to study the interrater reliability of a new guide — the Mobile App Development and Assess… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
3
0
2
Order By: Relevance
“…In relation to this particular issue, mobile health-related applications have been suggested as an alternative to provide easy, immediate access to the treatments that are needed [ 29 ]. However, not all available health-related mobile apps have been developed on the basis of scientific tenets [ 30 ] following available guides, and undergoing usability tests and efficacy studies [ 31 ]. Therefore, additional studies are needed to improve the development of data-based health-related mobile apps and facilitate a wider implementation and use among healthcare professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this particular issue, mobile health-related applications have been suggested as an alternative to provide easy, immediate access to the treatments that are needed [ 29 ]. However, not all available health-related mobile apps have been developed on the basis of scientific tenets [ 30 ] following available guides, and undergoing usability tests and efficacy studies [ 31 ]. Therefore, additional studies are needed to improve the development of data-based health-related mobile apps and facilitate a wider implementation and use among healthcare professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 15 of the included articles, a quality assurance system or a quality assessment tool was developed (10,21,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Five of the included articles were validation studies (8,(41)(42)(43)(44). In addition to development and validation studies, a number of studies (n = 39) were identified in which quality assessment tools were applied.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to this particular issue, the so-called new technologies (e.g., mobile apps) have been suggested as an alternative [41] although not all pain-related mobile apps have been developed on the basis of scientific tenets [42], and most have not been tested before dissemination [43]. Therefore, not all can be used safely [44]. However, studies show that mobile apps can effectively help to measure pain, (e.g., [30]), and self-manage different pain conditions, such as back pain [45], fibromyalgia [46] or cancer-related pain [47].…”
Section: Discussionmentioning
confidence: 99%